Desiccation and storage of Caenorhabditis elegans for use in aquaculture - Sauci Jimenez, M; Muñoz Ruiz, M.J; Brokate Llanos, A.M. (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
Aquaculture is a thriving sector, although the main issues it faces at the moment is the feeding of fish at an early stage of development. The most utilised specie for that is Artemia. Nematodes could replace Artemia in larviculture thanks to its rapid development by self-fertilization and its ability to be produced in a massive way fed with bacteria. Therefore, it would reduce the price of the raw. The use of nematodes for feeding fish larvae in aquaculture has required an adaptation to different salt concentrations in liquid medium. There is also necessary to develop an efficient protocol for the desiccation and storage of nematodes at different larval stages, this would allow the product to be transported to fish farms worldwide. We are developing desecating protocols for different conditions such as time, temperature and relative humidity. In this way we will be able to determine which of them is the most effective